Front Cover: Shortlisting SARS‐CoV‐2 Peptides for Targeted Studies from Experimental Data‐Dependent Acquisition Tandem Mass Spectrometry Data. Issue 14 (20th July 2020) - Gouveia, Duarte; Grenga, Lucia; Gaillard, Jean‐Charles; Gallais, Fabrice; Bellanger, Laurent; Pible, Olivier; Armengaud, Jean
Abstract : DOI: 10.1002/pmic.202000107 Identifying as quickly as possible the SARS‐CoV‐2 virus is of utmost importance for improving COVID‐19 diagnostic and for securing places where virus could be present. Tandem mass spectrometry may represent an interesting alternative to current diagnostic tools. In article number 2000107 by Duarte Gouveia et al., a list of SARS‐CoV‐2 peptides is established and prioritized in terms of mass spectrometry signal, sequence conservation amongst all known coronavirus genomes, and hydrophobicity characteristics. A shortlist of 14 peptides from the N, S, and M main structural proteins is recommended for developing mass spectrometry detection assays.